China’s normative power in managing South China Sea disputes - Han, David Guo Xiong (2020)
While existing studies show that China has been a norm-taker in accommodating to the norms of the Association of South East Asian Nations (ASEAN) to manage the South China Sea disputes, the possibility of China as a normative power in shaping ASEAN norms in the context of China–-ASEAN relations has received less attention. This article shall argue that China has sought to socialise ASEAN to recognise China as a normative power by accepting China’s preference for direct bilateral negotiations to handle the disputes while maintaining status quo and non-binding multilateral cooperation. To achieve this objective, throughout the 1990s and early 2000s, China initially adopted ASEAN norms of consensus-based, minimalist multilateralism to earn respectful reciprocation from ASEAN towards China. Subsequently, China sought to socialise ASEAN to recognise a new norm which posits that China, as a benign and responsible power, has the hierarchical primacy and legitimacy to set the pace and direction for handling the South China Sea disputes. Nevertheless, China’s attempts have been met with limited success. By insisting on direct bilateral negotiations which eschew a legally binding and multilateral solution to the territorial spat, China’s actions have challenged ASEAN norms of multilateralism and ASEAN centrality. As a result, ASEAN has reasserted its centrality and consensus-based multilateral diplomacy to steer the management of the disputes. Additionally, China’s increased maritime activities in the South China Sea and conflicting foreign policy messages have further undermined China’s credibility as a normative power to socialise ASEAN.